The ghost and the bogus bestseller - Coyle, Cleo (Kimberly, Alice. Haunted bookshop mystery., 2018)
"After an elegant new customer has a breakdown in her shop, Penelope suspects there is something bogus behind the biggest bestseller of the year. This popular potboiler is so hot that folks in her tiny Rhode Island town are dying to read it--literally. First one customer turns up dead, followed by another mysterious fatality connected to the book, which Pen discovers is more than just fiction. Now, with the help of her gumshoe ghost, Pen must solve the real-life cold case behind the bogus bestseller before the killer closes the book on her."--Back cover.